Analisis Kinerja Pengelola Keuangan Pemerintah Daerah Kota Malang Tahun Anggaran 2016-2020 - Ferian, Ferian Lazuardy Iman; Achmad, Komarudin (Telaah Ilmiah Akuntansi dan Perpajakan, 2024)
Local government is an institution that is tasked with regulating the economy of a region, one of which is in managing regional finances. Regional finances are determined in the form of the Regional Revenue and Expenditure Budget (APBD). This study aims to determine how the performance of local government financial management of Malang City for the 2016-2020 fiscal year, especially the financial capacity of Malang City Government in supporting regional autonomy. This research is a case study research with data collection using documentation techniques and literature study, and the data used is quantitative data in the form of the 2016-2020 Malang City Budget Realization Report which is obtained through the website https://bpkad.malangkota.go.id. Furthermore, this data is analyzed using financial ratios, namely the ratio of independence, effectiveness ratio, efficiency ratio, activity / compatibility ratio, and growth ratio.From the research, the writer got the information that based on the calculation of independence ratio, effectiveness, efficiency ratio, activity / harmony ratio, and growth ratio, it can be concluded that the financial capacity of Malang City is sufficient to support its regional autonomy. This can be seen from the autonomy ratio of the Malang City Regional Government, where at this level of independence it has a percentage that is in the sufficient category, this shows that the Regional Government of Malang City has slowly been able to reduce the role of the central government in providing funds to the Regional Government of Malang City. Abstract Pemerintah daerah merupakan suatu lembaga yang bertugas mengatur perekonomian suatu daerah salah satunya dalam mengelola keuangan daerah. Keuangan daerah yang ditentukan berupa Anggaran Pendapatan dan Belanja Daerah (APBD). Penelitian ini bertujuan untuk mengetahui bagaimana kinerja pengelolaan keuangan pemerintah daerah Kota Malang tahun anggaran 2016-2020 khususnya kemampuan keuangan Pemerintah Daerah Kota Malang dalam mendukung otonomi daerahnya. Penelitian ini merupakan penelitian studi kasus dengan pengumpulan data menggunakan teknik dokumentasi dan studi kepustakaan, dan data yang digunakan adalah data kuantitatif berupa Laporan Realisasi Anggaran Kota Malang Tahun 2016-2020 yang diperoleh melalui website https://bpkad.malangkota.go.id. Selanjutnya data ini dianalisis dengan menggunakan rasio keuangan yaitu rasio kemandirian, rasio efektivitas, rasio efisiensi, rasio aktivitas/keserasian, dan rasio pertumbuhan. Dari penelitian tersebut peneliti mendapat informasi bahwa berdasarkan perhitungan rasio kemandirian, rasio efektivitas, dan efisiensi, rasio aktivitas/keserasian, serta rasio pertumbuhan dapat disimpulkan bahwa kemampuan keuangan Kota Malang sudah cukup dalam mendukung otonomi daerahnya. Hal ini dilihat dari rasio kemandirian Pemerintah Daerah Kota Malang yang dihasilkan sebesar 35,79%, dimana pada tingkat kemandirian ini memiliki persentase yang masuk dalam kategori cukup, ini menunjukkan bahwa Pemerintah Daerah Kota Malang secara perlahan sudah dapat mengurangi peran pemerintah pusat dalam pemberian dana kepada Pemerintah Daerah Kota Malang.